Pelatihan Motion Graphics Berbasis Canva Untuk Meningkatkan Daya Saing Kreatif Siswa SMK Azizi - Arief Rahman Hakim; Khairul Fadhli Margolang; Yuni Franciska Br. Tarigan; Lathifah Tsamratul Ain; Nahdah Salsabiil Damanik; Hafni Zahra (STIKES Columbia Asia Medan, 2025)
The gap between vocational students’ competencies and the needs of the digital creative industry requires efforts to enhance students’ technological and creative skills. This community service program aimed to improve the digital competence and creativity of vocational students through Canva-based motion graphics training. The program was conducted at SMK Swasta Nur Azizi Tanjung Morawa using lectures, demonstrations, hands-on practice, and mentoring methods. The results showed that participants were able to understand bassic motion graphics concepts and produce simple animated works using Canva. Evaluation results indicated that more than 80% of participants were able to operate Canva’s basic animation features, and all participants successfully produced at least one motion graphics project, with an average competency improvement of approximately 30% compared to pre-training levels. Overall, the training proved effective in enhancing students’ creative skills, confidence, and readiness to meet the demands of the digital creative industry.